Growing Population in Punjab: The Policy Failures and the Associated Challenges - Arfeen, Bushra (Journal of Public Policy Practitioners, 2025)
Despite a long-standing history of population policies and initiatives in Punjab, the most populous province of the country continues to struggle with high fertility rates and a rapidly growing population. This paper explores the factors that hamper the success of the population policies in the province through primary interviews, policy documents and secondary sources to enhance the validity of the research. The findings of the study highlight that while the policies have evolved over time, the implementation mechanism remains weak in nature due to governance challenges, insufficient resources, misplaced priorities, political instability and coordination issues. Moreover, the cultural restrictions coupled with the religious factor in addition to the state of compromised female autonomy and service delivery challenges have also contributed towards the unmet need for family planning. The paper asserts that these factors indicate towards a systemic failure and proposes the need for greater collaboration, cultural acceptance, incorporation of women empowerment within the agenda of family planning, a stronger financial commitment and a long-term serious commitment.